Konflikty destruktywne – trudno rozwiązywalne w perspektywie „wychowania do wartości” - Cywińska, Małgorzata (Studia Edukacyjne, 2019)
Postmodernity born as a result of the crisis of civilization culture is characterized by pluralism, a “category” of difference, reflected, among others, in social (interpersonal, group) conflicts with a constructive and/or destructive impact. Special attention should be paid to difficult-to-solve conflicts due to their extremely unfavorable social consequences. They are characterized by a great complexity of disputable issues, aggression, violence, mutual harm, desire to destroy the opponent, a very escalating character. The persistence of such conflicts causes a sense of hopelessness on the part of the parties involved. Extinguishing or trying to resolve these situations requires extraordinary measures, as traditional dispute resolution strategies such as negotiation and mediation are not effective. “Education for values”, which focuses on identifying fundamental values, cannot be overestimated in the prevention of conflicts that are difficult to resolve. Large differences in values often trigger a conflict process, which is why it is so important to identify a universe accepted by all, which may become a significant inhibitor of hostilities and antagonisms.